An Easy-to-Array Respiration Sensor Based on Coupled Static Current Field. Issue 2 (April 2021) - Zeng, Minghui; Ren, Xi; Liu, Changlin
Abstract: Respiration detection is an important detection method in the diagnosis and treatment of diseases in the future. A sensor device with respiratory dynamic characteristics sensing and chemical composition sensing will provide more information for respiration analysis. In this paper, a gas sensor based on a coupled electrostatic field and flow field is proposed. The sensor uses flow field drift and electrostatic field polarization and migration to achieve selectively separation and detection of charged droplets. This sensing principle ensures that the device has a faster recovery time than a device based on the adsorption, and is more suitable for the needs of respiration detection.